Germas Behavior In The Work Area Of Bandar Seikijang Puskesmas, Pelalawan District - Kiki Megasari; Yulrina Ardhiyanti (Science Midwifery, 2022)
The Germas program is an effective measure to preventincreasing mortality and morbidity due to disease, therefore it is necessary to carry out a synergistic program to encourage people to live healthy lives. The highest achievement rate for carrying out GERMAS activities in Riau is Pekanbaru City 76.5%, but the target achievement in several districts in Riau Province is still far from the target such as in Kampar Regency 68.3% while the lowest GERMAS achievement of several districts in Riau province from the target figure The Strategic Plan of the Ministry of Health is Pelalawan Regency 65%. GERMAS at the Bandar Seikijang Health Center has never reached the target set by the government, which is 80%. This type of research is quantitative with a cross sectional design. The population is the Head of the Family (KK) who live in the Bandar Seikijang Health Center Work Area in 2019 with a total of 6,338 families, a sample of 95 families. The sampling technique was purposive sampling. The research instrument used a questionnaire. Data analysis was performed univariate and bivariate with chi-square test (α=0.05). The results of the bivariate analysis showed that there was a significant relationship between knowledge (ρ = 0.030 = 0.05), attitudes (ρ = 0.008 = 0.05), motivation (ρ = 0.020) = 0.05), media information (ρ =0.002 =0.05), the role of health workers (ρ =0.028˂α=0.05), and the role of the community environment (ρ =0.009 =0.05) with GERMAS behavior. It can be concluded that knowledge, attitudes, motivation, information media, the role of health workers, the role of the community environment are related to GERMAS behavior. So it is suggested that the Puskesmas can improve public services in order to increase public awareness of the importance of the GERMAS program that has been set by the government.